The Role of Forensic Medicine in Child Death Review Systems: A Comparative Review of Japan and Korea - Kyu-hee Jung; Kyung-moo Yang; Heesong Kim; In-Seok Choi (Korean Journal of Legal Medicine, 2026)
Child death review (CDR) requires determining whether accounts of a child’s death are consistent with objective postmortem findings, which in turn requires access to forensic information and qualified expertise. On August 4, 2026, amendments to Korea’s Child Welfare Act established a statutory framework for analyzing suspected child abuse deaths, and the revised Enforcement Decree included medical expertise among the eligibility criteria for special committee membership. The form and scope of forensic participation remain undefined. In this narrative policy review, we examine Japan’s two-level system, in which local governments review cases and a national committee aggregates questionnaires and local reports and conducts selected interviews; 21 national reports covered 1,506 cases involving 1,745 children. Forensic research at Chiba University demonstrated the importance of judicial autopsy information and contributed to national CDR policy discussions. In Korea, a multidisciplinary National Forensic Service team applied standardized internal coding to all autopsied child deaths between 2015 and 2021. The team classified 1,147 deaths as abuse-related under broader forensic screening criteria, compared with 243 deaths in official statistics. These totals are not directly comparable because ascertainment routes, criteria, and age ranges differ. Japan’s experience illustrates the need to connect local review and national aggregation with forensic evidence; Korea has developed an autopsybased data and expertise base. We propose seven roles for forensic medicine and priorities for integrating forensic expertise into the statutory framework.